Ticks and tick-borne pathogens at the cutaneous interface: host defenses, tick countermeasures, and a suitable environment for pathogen establishment - Wikel, Stephen (Frontiers in Microbiology, 2013)
Ticks are unique among hematophagous arthropods by continuous attachment to host skin and blood feeding for days; complexity and diversity of biologically active molecules differentially expressed in saliva of tick species; their ability to modulate the host defenses of pain and itch, hemostasis, inflammation, innate and adaptive immunity, and wound healing; and, the diverse array of infectious agents they transmit. All of these interactions occur at the cutaneous interface in a complex sequence of carefully choreographed host defense responses and tick countermeasures resulting in an environment that facilitates successful blood feeding and establishment of tick-borne infectious agents within the host. Here, we examine diverse patterns of tick attachment to host skin, blood feeding mechanisms, salivary gland transcriptomes, bioactive molecules in tick saliva, timing of pathogen transmission, and host responses to tick bite. Ticks engage and modulate cutaneous and systemic immune defenses involving keratinocytes, natural killer cells, dendritic cells, T cell subpopulations (Th1, Th2, Th17, Treg) , B cells, neutrophils, mast cells, basophils, endothelial cells, cytokines, chemokines, complement, and extracellular matrix. A framework is proposed that integrates tick induced changes of skin immune effectors with their ability to respond to tick-borne pathogens. Implications of these changes are addressed. What are the consequences of tick modulation of host cutaneous defenses? Does diversity of salivary gland transcriptomes determine differential modulation of host inflammation and immune defenses and therefore, in part, the clades of pathogens effectively transmitted by different tick species? Do ticks create an immunologically modified cutaneous environment that enhances specific pathogen establishment? Can tick saliva molecules be used to develop vaccines that block pathogen transmission?